Integrated Transcriptomic and Bioinformatics Analyses Reveal the Molecular Mechanisms for the Differences in Seed Oil and Starch Content Between Glycine max and Cicer arietinum - Cheng, Kun; Pan, Yi-Fan; Liu, Lü-Meng; Zhang, Han-Qing; Zhang, Yuan-Ming (Frontiers in Plant Science, 2021)
Seed oil and starch content of soybean is significantly different from that of chickpea. However, there are limited studies on its molecular mechanisms. To address this issue, we conducted integrated transcriptomic and bioinformatics analyses for species-specific genes and acyl-lipid-, starch-, and carbon-metabolism-related genes. Among seven expressional patterns of soybean-specific genes, four were highly expressed at the middle and late oil accumulation stages; these genes significantly enriched fatty acid synthesis and carbon metabolism, and along with common ACCase highly expressed at soybean middle seed development stage, common starch degrading enzyme BAM5 highly expressed at soybean early seed development stage, and oil-synthesis-related genes ACCase, KAS, KAR, ACP and LACS co-expressed with WRI1, they may result in high seed oil content and low seed starch content in soybean. The common AGPase highly expressed at chickpea middle seed development stage, along with more starch biosynthesis genes co-expressed with four-transcription-factor homologous genes in chickpea than in soybean and the common WRI1 no co-expressed with oil synthesis genes in chickpea, they may result in high seed starch content and low seed oil content in chickpea. The above results may be used to improve chickpea seed oil content in two ways. One is to edit CaWRI1 to co-express with oil-synthesis-related genes, which may increase carbon metabolites flowing to oil synthesis, and another is to increase the expression levels of miRNA159 and miRNA319 to inhibit the expression of MYB33, which may down-regulate starch-synthesis-related genes, making more carbon metabolites flow into oil synthesis. Our study will provide a basis for future breeding efforts to increase the oil content of chickpea seeds.